Therapeutic management of Argulosis in Carp ponds, Andhra Pradesh, India - Ramudu, Kurva Raghu; Devi, B Chamundeswari; Kumar, B Pavan (International Journal of Medicine, 2015)
Background: The genus Argulus sp. belongs to class Crustacea (Branchiura), which is commonly called as fish louse. These are common parasites on freshwater fish like carps (Both Indian Major Carps and Exotic Carps).Objectives:The aim of present study is to determine the prevalence, severity of infestation and control measures of Argulosis in Carp ponds.Results: In the present work about 233 fishes were examined, 53 were found infected (22.74%) and severity of infestation varied from 0.5 to 2. Argulus sp. were found and infected various organs such as dorsal fins, anal fin, pectoral fins, pelvic fins and head region of carps.Conclusion: The present study also, brings about the conclusion that the prevalence rate of Argulus sp. is high in Labeo rohita followed by Cirrhinus mrigala and Catla catla respectively.Â